How things work today - Wright, Michael; Patel, Mukul (London Marshall Editions Ltd., 2000)
The book is arranged in thematic chapters, but extensive cross-referencing emphasizes the multiple applications of various technologies. For example, most TV sets are based on the cathode-ray tube, in which a beam of high-speed electrons is directed towards a target (the screen) and similar technology can be found in the giant particle accelerators used by research physicists. A principles section provides an introduction to the basic science that underlies modern technology--matter, electricity and magnetism, light, electronics, and mechanics. Concise definitions of common scientific and technological terms are provided in a glossary. And at the end of the book, a list of world wide web addresses provides gateways to much more information.
Includes index
FA-3590g donated by Prof. Dante Cruz
Keywords: Technology -- Popular works